Tensile properties of PLA/PBAT blends and PLA fibre-reinforced PBAT composite - Eakasit Sritham; Phakaimat Phunsombat; Jedsada Chaishome (My University, 2018)
The tensile properties of PLA/PBAT blends, PLA fibre reinforced PBAT composite (PLAF) at room temperature and -18°C were investigated. The concentrations of PLA in the blends were 10%, 20%, 30% and 40% (by volume). There was an improvement of elastic modulus (E) for PLA/PBAT blends when PLA was 40%. There was no significant difference of ultimate tensile strength ( UTS ) among the blends. For the same concentration of PLA (40%) in PLA-PBAT mixture, PLAF exhibited higher values of E and UTS than that of PLA/PBAT blends. Elongation of PLA/PBAT blends rapidly decreased upon the addition of PLA to the blends. The values of E and UTS for PLA/PBAT blends and composite, neat PLA, and PP increased with the decreasing of temperature from room temperature to -18°C. The effect of decreasing temperature was not observed on elongation. It was appeared from the results obtained for FTIR and DSC measurements that PLA and PBAT were immiscible, separating into two phases.
Keywords: Elongation; biodegradable polymer synthesis and properties